Cutaneous granular cell tumor: A case report - Deliya Paudel; Ram Chandra Adhikari (Association of Clinical Pathologists of Nepal, 2019)
Granular cell tumor is a rare benign neoplasm of the skin that accounts for 0.5% of all soft-tissue tumors. Granular cell tumor can affect both sexes and in any age, although it is most common in females. The common locations are the head and neck, the tongue is affected in 25% of cases but any internal organs can be affected such as soft tissue, bronchus, stomach, rectum, anus, biliary ducts. Here, we report a 58-year-old female patient who presented with a 4-year history of a slowly growing mass, with a dimension of 5 × 4 cm on her left waist, diagnosed as a Granular cell tumor at histopathological examination.